Logic-Based Therapy and Everyday Emotions: A Case-Based Approach - Cohen, Elliot D. (Lexington Books, 2016)
In this latest book on the popular philosophical practice modality of Logic-Based Therapy, LBT inventor and practitioner, Elliot D. Cohen, develops both theory and practice of LBT within the context of accessible, engaging, and illustrative cases involving everyday emotions, such as anxiety, worry, guilt, anger, and sadness. Beginning with an examination of the relationship between philosophical and psychological practice, Cohen shows how philosophy (its methods and theories) can be applied, through the practice of LBT’s six-step method, to help people confront the emotionally-laden problems of everyday life with courage, temperance, empathy, prudence, and the other “Guiding Virtues” of LBT. In non-technical language, accessible to students of philosophy and psychotherapy as well as professionals in these fields, Cohen artfully builds a mutually cooperative, competent, and compassionate bridge between philosophical and psychological practice.